Shaping the text and the work: Printers and men working behind the scenes in the 16th century (Carte Romanze, 2024)
The contributions in this volume sketch the figures of the printers and booksellers who produced books and made them identifiable to 16th-century buyers and readers. Whether facing censorship or paper shortages, prosperity or the brink of bankruptcy, they developed publishing strategies that enabled them to diversify and expand their readership. This book provides a better understanding of the men and women who shaped the language, literature and reading practices of the late Middle Ages and Renaissance.
Keywords: Printers; Booksellers; Renaissance; Late Middle Ages; Bibliography; textual criticism; Literature